Phase II study of transcatheter arterial chemoembolization (TACE) combined with apatinib for advanced perihilar cholangiocarcinoma - Hao Li; Pengfei Chen; Mengfan Zhang; Zhengfeng Wang; Yanbang Lian; Baohong Wen; Jianzhuang Ren; Xinwei Han; Bingjie Li; Xuhua Duan (Scientific Reports)
Abstract To confirm transcatheter arterial chemoembolization (TACE) combined with apatinib for advanced perihilar cholangiocarcinoma (PCC) is effective and safe. A comprehensive treatment plan involving TACE combined with targeted therapy was implemented for the patients with pathologically diagnosed advanced PCC, where TACE was performed every 4–6 weeks to deliver albumin paclitaxel and gemcitabine for a maximum of six times. Oral apatinib was administered in between TACE cycles. The main endpoint of this study was the objective response rate (ORR), and the secondary endpoints were progression free survival (PFS), overall survival (OS), and adverse events. Kaplan-Meier method was used to assess survival risk factors. From November 2019 to October 2020, a total of 41 patients were enrolled with perihilar cholangiocarcinoma who were pathologically diagnosed. All underwent TACE treatment and received at least two treatment cycles. As of October 2022, the median follow-up period of this study was 28.3 months, the ORR of this study reached 56.1% (95% CI 39.7–71.5%); DCR reached 90.2% (95% CI 76.9–97.3%), and the median PFS was 9.7 months (95% CI 7.6–11.8 months), the median OS was 16.5 months (95% CI 13.6–19.3 months). The treatment-related adverse events (AEs) in this study were mild, mainly Grade 1 or 2. Among the most common AEs were bone marrow suppression and hand-foot syndrome, while no patient had Grade 4 AE. Comprehensive treatment combining TACE with apatinib for advanced PCC had favorable therapeutic effects, and no major safety issue was observed in the patients enrolled.